Financial services to the poor: the microfinance dilemma in Andhra Pradesh. Issue 7 (2nd October 2016) - Gajjala, Venkataramana; Gajjala, Radhika
ABSTRACT: In India, microfinance and associated strategies of forming self-help groups came about in response to a newly independent nation and its need to include the rural non-banking population into national structures of development and governance. This article examines how the rapid growth of microfinance institutions during the last two decades – especially in the context of the more recent transition from non-profit to for-profit non-banking finance companies (NBFCs) – has led to a significant increase in the delivery of financial services to the rural poor. In Andhra Pradesh, the simultaneous existence of some of India's most prominent microfinance institutions (MFIs) and their mobilisation of self-help groups – with state backing and linkages to banks leading to relatively easy availability of funds – has led to a tremendous surge in the availability of credit across the state.